A survey of the East Palaearctic Gnaphosidae (Araneae). 12. A review of Sidydrassus Esyunin & Tuneva, 2002 - Fomichev, Alexander A. (Zootaxa)
The gnaphosid spider genus Sidydrassus Esyunin & Tuneva, 2002 is currently known to contain only three species: S. shumakovi (Spassky, 1934) (♂♀, the type species), S. tianschanicus (Hu & Wu, 1989) (♂♀) and S. rogue Tuneva, 2004 (♂). A revision of new material has revealed one more species, S. saiynovi sp. n. (♂) from Kazakhstan. Furthermore, the previously unknown female of S. rogue is described. The redescriptions and new faunistic records of S. shumakovi and S. tianschanicus are provided as well, and the known distribution of the genus is mapped. The defining key to Sidydrassus species is provided and possible relationships within the genus are briefly discussed.